p130Cas/BCAR1 and p140Cap/SRCIN1 Adaptors: The Yin Yang in Breast Cancer? - Centonze, Giorgia; Natalini, Dora; Salemme, Vincenzo; Costamagna, Andrea; Cabodi, Sara; Defilippi, Paola (Frontiers in Cell and Developmental Biology, 2021)
p130Cas/BCAR1 is an adaptor protein devoid of any enzymatic or transcriptional activity, whose modular structure with various binding motifs, allows the formation of multi-protein signaling complexes. This results in the induction and/or maintenance of signaling pathways with pleiotropic effects on cell motility, cell adhesion, cytoskeleton remodeling, invasion, survival and proliferation. Deregulation of p130Cas/BCAR1 adaptor protein has been extensively demonstrated in a variety of human cancers in which overexpression of p130Cas/BCAR1 correlates with increased malignancy. p140Cap (p130Cas associated protein), encoded by the SRCIN1 gene, has been discovered by affinity chromatography and mass spectrometry analysis of putative interactors of p130Cas. It came out that p140Cap associates with p130Cas not directly but through its interaction with the Src Kinase. p140Cap is highly expressed in neurons and to a lesser extent in epithelial tissues such as the mammary gland. Strikingly, in vivo and in vitro analysis identified its tumor suppressive role in breast cancer and in neuroblastoma, showing an inverse correlation between p140Cap expression in tumors and tumor progression. In this review, a synopsis of 15 years of research on the role of p130Cas/BCAR1 and p140Cap/SRCIN1 in breast cancer will be presented.